Applications of fluorescence in situ hybridization (FISH) in genome research - Nhu Phuong, Hoang Thi; Thu Hue, Huynh Thi; Xuan Hieu, Cao (Vietnam Journal of Biotechnology, 2020)
Fluorescence in situ hybridization (FISH) technique enables the direct detection of DNA sequences inintact cellular materials (e.g. individual chromosomes in metaphase spreads). This review article focuses on theapplications of FISH in genome research, including validation and correction of the genome assembly from thenext-generation sequencing (NGS) projects. DNA probes for specific DNA fragments of the assembly can beobtained from PCR amplicon or cloned products using different vector systems. Localization of these probeson their respective chromosomal regions can be visualized by FISH, providing useful information to crosscheckthe assembly data. Furthermore, the recent refinements in the FISH technology including using smartpooling scheme of differently colored DNA probes, together with consecutive FISH experiments (stripping andreprobing of the same slide) are described. These advances in multicolor FISH can provide crucial linkageinformation on association of linkage groups and assembly scaffolds, resulting in so-called cytogenetic maps.Integration of the cytogenetic maps and assembly sequences assists to resolve the chromosome-level genomeassembly and to reveal new insights in genome architecture and genome evolution. Especially, comparativechromosome painting with pooled DNA probes from one reference species can be used to investigate ancestralrelationships (chromosome homeology and rearrangements) among other not-yet-sequenced species. Inaddition, FISH using DNA probes for certain specific classes of repetitive DNA elements as well as for basicchromosome structures (e.g. centromere or telomere DNA repeats, ribosomal DNA loci) can be used to studythe genome organization and karyotype differentiation. We also discussed about limitations and futureperspectives of the FISH technology.